DEVELOPING ESP MATERIALS FOR TOURISM INDUSTRY IN MALANG - Masyhud Masyhud; Khoiriyah Khoiriyah (PROJECT (Professional Journal of English Education), 2021)
This article explores the need for English as a mean of communication for the tourism industry in Malang. Since the need for English speaking skills is immensely demanded, this community service program was proposed to provide a ready-use module to facilitate the locals practising their English speaking skills. Hence, this study reported on-going project designing English for Specific Purposes (ESP) materials for the tourism industry in Malang. It is implemented in three stages: planning stage, implementation stage and evaluation. Specifically, the target learners are Karang Taruna members who are working in tourism near Kelurahan Jodipan. Since there are many thematic villages there, the learning content is designed contextually with the local wisdom and local culture. Hence, it is projected to help the locals provide better services for their visitors, especially foreign visitors.